Factors in the Neonatal Period Associated With Pulmonary Hypertension at 28 Days of Life in Broncho-Pulmonary Dysplasia - Nguyen Thi Hai Anh MD; Tran Minh Dien PhD; Le Thi Ha MD; Pham Thao Nguyen MD; Dang Thi Hai Van PhD (Global Pediatric Health, 2024)
Objectives. To identify factors associated with pulmonary hypertension (PH) at 28 days of life in preterm infants with bronchopulmonary dysplasia (BPD). Methods . This observational study included 128 premature infants with BPD between January 2022 and February 2023 from the neonatal intensive care unit of Vietnam National Children’s Hospital. Results . PH was observed using echocardiography in 29 patients (22.66%). The prevalence of severe BPD in the PH group (62.07%) was significantly higher than that in the non-PH group (18.18%). The multivariate logistic regression showed 2 predictors of PH in BPD: invasive mechanical ventilation up to 28 days of life (odds ratio [OR]:9.440; 95% confidence interval [CI]: 3.090-28.833; P  < .001) and history of shock (OR: 2.962; 95% CI: 1.067-8.225; P  = .037). Conclusion. We found 2 predictors of PH at 28 days of life in BPD: invasive mechanical ventilation up to 28 days of life and history of shock.